2023
DOI: 10.1242/jeb.200261
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral algorithms and neural mechanisms underlying odor-modulated locomotion in insects

Abstract: Odors released from mates and resources such as a host and food are often the first sensory signals that an animal can detect. Changes in locomotion in response to odors are an important mechanism by which animals access resources important to their survival. Odor-modulated changes in locomotion in insects constitute a whole suite of flexible behaviors that allow insects to close in on these resources from long distances and perform local searches to locate and subsequently assess them. Here, we review changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 207 publications
0
3
0
Order By: Relevance
“…Might animals, such as flying insects, use whiff statistics to estimate the distance to a source? The qualitative changes exhibited by flying insects when they get close to a source [ 23 , 26 ] indicate that there is probably at least a correlational mechanism linking their olfactory experience with their behavioural decision to approach visual features [ 8 , 24 ]. In our experiments, we achieved an accuracy of 3–8 m, depending on the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Might animals, such as flying insects, use whiff statistics to estimate the distance to a source? The qualitative changes exhibited by flying insects when they get close to a source [ 23 , 26 ] indicate that there is probably at least a correlational mechanism linking their olfactory experience with their behavioural decision to approach visual features [ 8 , 24 ]. In our experiments, we achieved an accuracy of 3–8 m, depending on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies have shown that animals do modulate plume tracking decisions based on a time history of odour encounters [ 21 , 22 ]. Furthermore, animals qualitatively change their behaviour when they get close to the source, including flying insects [ 23 ], which approach visual features when they get close [ 8 , 24 ], and dogs [ 25 ] that modulate their search speed (see also [ 26 ] for a review). These observations suggest that animals are able to extract information about source distance from their olfactory experience, either in the form of a true distance estimate or through a simple correlative heuristic.…”
Section: Introductionmentioning
confidence: 99%
“…Might animals, such as flying insects, use whiff statistics to estimate the distance to a source? The qualitative changes exhibited by flying insects when they get close to a source 23,26 indicate that there is likely at least a correlational mechanism linking their olfactory experience with their behavioral decision to approach visual features 8,24 . In our experiments we achieved an accuracy of 3-8 meters, depending on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies have shown that animals do modulate plume tracking decisions based on a time history of odor encounters [21,22]. Furthermore, animals qualitatively change their behavior when they get close to the source, including flying insects [23], which approach visual features when they get close [8,24], and dogs [25] that modulate their search speed (see also [26] for a review). These observations suggest that animals are able to extract information about source distance from their olfactory experience, either in the form of a true distance estimate or through a simple correlative heuristic.…”
Section: Introductionmentioning
confidence: 99%
“…Olfaction plays an important role in host location as well as mating in insects (Wechsler and Bhandawat, 2023 ). The antennae and labial palps are the main appendages on the head for detecting volatile semiochemicals (Wensler, 1974 , 1977 ; Bromley and Anderson, 1982 ; Pickett et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%